2015
DOI: 10.1002/biot.201400758
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the hematopoietic stem cell niche: Frontiers in biomaterial science

Abstract: Hematopoietic stem cells (HSCs) play a crucial role in the generation of the body’s blood and immune cells. This process takes place primarily in the bone marrow in specialized ‘niche’ microenvironments, which provide signals responsible for maintaining a balance between HSC quiescence, self-renewal, and lineage specification required for life-long hematopoiesis. While our understanding of these signaling mechanisms continues to improve, our ability to engineer them in vitro for the expansion of clinically rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 189 publications
0
106
0
Order By: Relevance
“…The LSK faction was collect in PBS + 25% FBS on ice and immediately used [19,29,46,[67][68][69][70].…”
Section: Hematopoietic Stem Cell Isolationmentioning
confidence: 99%
“…The LSK faction was collect in PBS + 25% FBS on ice and immediately used [19,29,46,[67][68][69][70].…”
Section: Hematopoietic Stem Cell Isolationmentioning
confidence: 99%
“…Moreover, mouse and human niches differ in some respects so that the cellular composition of artificial niches realizable in the mouse setting may not be transferable to the human situation. In addition, the extracellular matrix composition influences HSC differentiation, proliferation, lineage specification, and apoptosis [63][64][65][66]. The materials used in studies are therefore of utmost importance, and, as has been shown for some materials, may not be suitable for the in vitro culture of CD34 + cells [67].…”
Section: In Vitro-approachesmentioning
confidence: 99%
“…Collectively, these findings clearly demonstrate the importance of cell, matrix, and molecular cues from the endogenous niche in providing functionality to HSCs. Recent advances in tissue engineering to mimic the bone marrow niche showed promising, yet not conclusive, methods to maintain HSCs derived from bone marrow or cord blood [75]. Future efforts to mimic the authentic milieu of cell, matrix, and biomolecule cues by integrating novel tissue engineering approaches will be useful to maintain and expand HSCs.…”
Section: Role Of the Microenvironment In Direct Reprogrammingmentioning
confidence: 99%